Multimodality imaging of hematologic malignancies affecting the breast: a pictorial essay - Natalia Guerrero-Fajardo; Mane M. Ayala-Duran; Yesika J. Davila-Zablah; Nancy L. Garza-Garcia; Gabriela S. Gomez-Macias; Daniel F. Lopez-Altamirano; Margarita L. Garza-Montemayor (Journal of the Mexican Federation of Radiology and Imaging)
Hematologic malignancies affecting the breast are a heterogeneous group that includes lymphomas, leukemias, and multiple myeloma. Secondary infiltration by lymphoma is the most common hematologic malignancy of the breast. This pictorial essay presents clinical cases of mammography, ultrasound, and magnetic resonance imaging (MRI) findings of lymphoma, leukemia, and multiple myeloma, with histopathologic confirmation. The most common imaging findings were mass(es), non-mass lesions, or architectural distortion, and less commonly, diffusely increased breast density. There are no specific criteria for image diagnosis of hematologic malignancies affecting the breast; therefore, it is essential to know the medical history. Although a biopsy is always necessary, knowledge of the imaging findings gives the radiologist the necessary tools to diagnose correctly.